Pengaruh DER, CAR, dan ROE terhadap Peringkat Obligasi Perbankan yang Listing di PT Bursa Efek Indonesia pada Periode 2008-2013 - Debora Tri Oktarina Phety (Universitas Winaya Mukti, 2018)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Capital Adequacy Ratio (CAR) and Return on Equity (ROE) both partially and simultaneously to bank bond ratings. Bond rating agencies are needed to assess the performance of banks that issue bonds by providing information about the quality and risk of bonds. The phenomenon in Indonesia occurs when several issuers fail to pay but have a bond rating at the investment grade level. The risk of a default on bonds is seen in the case of a failure to pay PT Bank Global Tbk bonds where the Kasnic rating agent gave an A- rating, but when BI announced a freeze on Bank Global's license, the bond rating was reduced to D. This research used Ordered Logit Model (OLM) as a method of data analysis.The random sampling method was carried out as a sampling method. The results of this study showed two things. First, the Capital Adequacy Ratio (CAR) and Return on Equity (ROE) had a positive impact on the bond rating. Second, the Debt to Equity Ratio (DER) had a negative impact on the bond rating. Whilst simultaneously Debt to Equity Ratio (DER), Capital Adequacy Ratio (CAR), and Return on Equity (ROE) affected the bond rating.